Does Zakat Impact on Human Development Index? Empirical Evidence from Indonesia - Rusanti, Ega; Anindya, Annisa Sasri; Atiya, Nikmatul; Widiastuti, Tika (International Journal of Zakat, 2023)
The Human Development Index (HDI) is critical for measuring a country’s economic growth. This research aims to determine the impact of zakat distribution in five priority sectors, i.e., humanity, education, economy, health and religion, on Indonesia’s HDI. The data consists of zakat distribution and HDI for the 2012-2022 period. Ordinary Least Square (OLS) regression is used to analyze the relationship between variables using the EViews 12 tool. The distribution of zakat in the education and humanitarian sectors has a positive and significant effect on increasing HDI in Indonesia. Meanwhile, no impact is found on the economic sector, health and religion. Implications are drawn for zakat institutions and the government to formulate policies and programs to optimize zakat funds consistently and strategically in vital sectors.